Mogamulizumab: An Anti-CC Chemokine Receptor 4 Antibody for T-Cell Lymphomas. Issue 4 (April 2020) - Moore, Donald C.; Elmes, Joseph B.; Shibu, Priscila A.; Larck, Chris; Park, Steven I.
Objective: To review the pharmacology, pharmacokinetics, efficacy, safety, dosing, and administration of mogamulizumab for the treatment of T-cell lymphomas.Data Sources: A literature search of PubMed (1966 to September 2019) was conducted using the keywords mogamulizumab, KW-0761, and lymphoma . Data were also obtained from package inserts and meeting abstracts.Study Selection and Data Extraction: All relevant published articles, package inserts, and unpublished meeting abstracts on mogamulizumab for the treatment of T-cell lymphomas were reviewed.Data Synthesis: Mogamulizumab is an anti-CC chemokine receptor 4 (CCR4) monoclonal antibody that has demonstrated activity in various T-cell lymphomas. It was approved by the US Food and Drug Administration (FDA) for the treatment of adult patients with relapsed or refractory mycosis fungoides (MF) or Sézary syndrome (SS) who have been treated with at least 1 prior line of therapy. Mogamulizumab demonstrated significant improvement in progression-free survival compared with vorinostat in patients with relapsed or refractory MF or SS. Serious adverse events associated with mogamulizumab include infusion-related reactions, cutaneous drug eruption, and autoimmune complications. Mogamulizumab administration in the preallogeneic hematopoietic stem cell transplant setting can increase the risk for severe posttransplant graft-versus-host disease.Relevance to Patient Care and Clinical Practice: Mogamulizumab is a first-in-class CCR4 inhibitor, providing a new option in the treatment of relapsed or refractory cutaneous T-cell lymphomas. Although not currently FDA approved for this indication, mogamulizumab may have some utility for the treatment of relapsed adult T-cell leukemia/lymphoma.Conclusion: The recent approval of mogamulizumab represents an important addition to the armamentarium of pharmacotherapies for T-cell lymphomas.